Exploring the Relationship Between Palm Oil and Bioenergy - Judijanto, Loso (West Science Social and Humanities Studies, 2025)
The global pursuit of renewable energy has intensified interest in palm oil as a key bioenergy feedstock, particularly in biodiesel production. This study explores the evolving relationship between palm oil and bioenergy through a bibliometric analysis of scientific publications indexed in the Scopus database. Using VOSviewer for data visualization, we examined keyword co-occurrence, temporal trends, thematic density, author collaboration networks, and institutional and country-level partnerships. The results reveal that research has transitioned from foundational topics such as greenhouse gas emissions and biodiesel to more advanced themes like anaerobic digestion, waste valorization, and biotechnological innovations. Malaysia and Indonesia emerged as leading contributors, both in publication volume and international collaboration, while emerging economies such as Brazil and Thailand show increasing engagement. The study provides practical insights for policymakers, industry stakeholders, and researchers by mapping knowledge clusters and highlighting research gaps. It also contributes theoretically by integrating environmental, technological, and socio-political perspectives on palm oil-based bioenergy systems. Limitations include database constraints and the exclusion of non-English literature. Overall, this study offers a timely and comprehensive overview of how palm oil is positioned within global bioenergy discourses and provides a foundation for more sustainable and inclusive energy transitions.